Implementasi Mediasi Melalui Peradilan Agama dalam Penyelesaian Sengketa Rumah Tangga Berpoligami di Pengadilan Agama Rantau Prapat - Fikri Bayu Siregar (Ar-Raniry: International Journal of Islamic Studies, 2021)
The purpose of this study was to determine the implementation of mediation through the religious courts in the settlement of polygamous household disputes at the Rantau Prapat religious court. Especially about how it is planned, what are the steps, what are the inhibiting and supporting factors, and why mediation is needed at the Rantau Prapat religious court. The research method uses a descriptive qualitative approach. The results showed that; 1) counselee planning at the religious court of Labuhan Batu Regency in reducing the number of polygamous disputes is carried out in two plans, namely based on service culture and based on transformative culture. 2) Mediation steps using Education and Consultative. 3) The supporting factors are the facilities and infrastructure, the tools or instrumentals used, the existence of understanding material about the importance of the sakinah family as well as an evaluation of technical implementation. While the inhibiting factors are the lack of awareness of some people to participate in the sakinah family program, less than optimal empowerment, less than optimal support from P3K, not yet optimal provision of constructive sakinah family development activities through the sakinah family festival, 4) the need for mediation as a solution to reduce the number of polygamous disputes, which is based on behind by the existence of pressure from Islamic communities or organizations and the desire for one's rights.